Implementing psychosocial methods to reinforce women's legal rights awareness training in Jordan. Issue 3 (November 2015) - Darras, Lina; van der Heide, Roza
Abstract : There are often large gaps between providing information on legal rights and the actual use of that information in women's daily lives. Clinical psychologists from the Arab Renaissance for Democracy and Development - Legal Aid devised joint psychosocial legal awareness training sessions to empower women through culturally sensitive assertiveness skills training, so they could make better practical use of legal rights information. Training of trainers sessions were held with Family Guidance Awareness Center lawyers and social workers, who conducted an anecdotal study with women from the community of Zarqa, Jordan to verify two different methods. The first method involved conducting both legal awareness and a psychosocial session on the same day. The second method, utilised modules, both legal and psychosocial, spread over the course of two days. Quotes from participants strongly suggest that women are able to make better use of legal information if provided with a supportive, skills based psychosocial session as an adjunct, it also suggested that it is likely that longer information and longer psychosocial training sessions (method 2) result in the best outcomes, so long as there is a sufficient break between sessions to overcome fatigue. However, before more widespread implementation of these methods, we recommend more longitudinal research, specifically focused on testing for unintended negative consequences, seeing how well changes can be generalised to fit into women's everyday lives, and how well they last over time.